The use of the water extract of Rosa spp petals as a bacterial growth medium - Ahmed A. M. Al-Azzauy; Dalya B. Hana; Mayssaa E. Abdalah (College of Pharmacy / Mustansiriyah University, 2011)
In a pioneer study, simple water extract for the red petals of Rosa spp. was prepared under sterile conditions, then used for the first time as experimental bacterial culture medium for the growth of the bacteria: Pseudomonas aeruginosa, Proteus vulgaris, Staphylococcus aureus, Escherichia coli, Streptococcus pneumoniae and Klebsiella pneumoniae; the medium was used as alternative culture medium for the routine culture media (Nutrient agar, MacConkey agar and blood agar) that used for the growth of these genera in the laboratories. All the genera showed active growth after 24 hours when it used directly as a liquid culture medium. The extract was used also to enrich the agar-agar and cultivated with the same bacteria; it showed a noticeable growth. The results suggest that this extract is a suitable culture medium; it could be used instead of the routine culture media that used in the cultivation of these bacteria in the laboratories. It also represents important, rich nutritional medium as those that is used in the routine laboratory work.